Spinibdella Thor - Hernandes, Fabio A.; Skvarla, Michael J.; Fisher, Ray; Dowling, Ashley P. G.; Ochoa, Ronald; Ueckermann, Edward A.; Bauchan, Gary R. (Zenodo, 2016)
Spinibdella Thor Spinibdella Thor, 1930b: 22; 1931a: 39; Atyeo, 1960a: 424; Soliman & Zaher, 1975: 80; Tseng, 1978: 38; Chaudhri et al ., 1979: 133; Michocka, 1987: 82. Type-species: Spinibdella reducta Thor, 1930b: 23 by original designation. 121. Spinibdella ampulla Wallace & Mahon, 1972: 568; Millstream, Western Australia, ex green herbaceous, couch grass, Eucalyptus sp. litter. Remarks. Male unknown. Type deposition. ANIC. 122. Spinibdella ankylotricha Omukunda, Theron & Ueckermann, 2012: 9; Limpopo Province, South Africa. Type deposition. NCA. 123. Spinibdella antarctica (Trägårdh, 1907): 24; South Georgia, Grytviken Peninsula, Antarctica, under rocks.— Wallace, 1970: 107. Original designation: Bdella antarctica Trägårdh; Thor, 1931a: 33. Redescription. Wallace (1970). Type deposition. BPBM; USNM, BMNH, ANIC. 124. Spinibdella arenosa Willmann, 1939b: 532; Germany (Wangerooge Island) (Willmann, 1952: 165). Type deposition. ZSM. 125. Spinibdella atyeoi Gupta & Paul, 1985: 14; West Bengal, Midnapur Dist., Patharkumkumi, India, ex nest of Prinia inornata (Sykes 1832) (Aves: Cysticolidae). Remarks. Male unknown. Type deposition. NZSI. 126. Spinibdella bifurcata Atyeo, 1960a: 430; 10 miles west of Tuxtla Gutierrez, Chiapas, Mexico, under rock.— Soliman, 1975: 48. Distribution. Mexico (Chiapas, Oaxaca, Puebla, Michoacán, United States (Texas) (Atyeo 1960a), Egypt (Giza) (Soliman 1975; Zaher 1986), Malaysia (Shiba 1978), China (Lin et al. 2006). Redescription. Shiba (1978). Type deposition. Holotype and paratypes at SEMC, paratypes at USNM, BMNH and SAM. 127. Spinibdella bioculata Swift & Goff, 1987: 39; Kahoolawe Island, Hawaii, ex Kiawe duff and grasses. Remarks. Male unknown. Type deposition. BPBM. 128. Spinibdella californica McGregor, 1956: 12; California, USA, ex lemon. Type deposition. Unknown. 129. Spinibdella corticis (Ewing, 1909a): 122; Urbana, Illinois, USA, under bark of cottonwood tree.— Atyeo, 1960a: 426. Original designation: Bdella corticis Ewing; Thor, 1931a: 36. Other name: ...